2021
DOI: 10.1055/a-1709-0280
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Durable, Self-Photosensitized Mononuclear Ruthenium Catalyst for CO2 Reduction

Abstract: A novel mononuclear ruthenium (Ru) complex bearing a PNNP-type tetradentate ligand is introduced here as a self-photosensitized catalyst for the reduction of carbon dioxide (CO2). When the pre-activation of the Ru complex by reaction with a base was carried out, an induction period of catalyst almost disappeared and the catalyst turnover numbers (TONs) over a reaction time of 144 h reached 307 and 489 for carbon monoxide (CO) and for formic acid (HCO2H), respectively. The complex has a long lifespan as a dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…We kicked off the project by investigating the possibility of CO 2 hydrogenation in alcoholic solvents, as similarly reported by Klankermayer and Beller, where acidic conditions were used by adding Al­(OTf) 3 or bistriflyl imide derivatives. In contrast, to be emphasized is that our system for CO 2 hydrogenation shows high reactivity under basic conditions (utilizing catalytic alkali base, vide infra and Table S5), capitalizing on our previous methods for the activation of (PNNP)­Ir precatalysts to initiate the catalyst vitalized by the positive effects of alkali bases in alcohols. , After an initial optimization of solvent, pressure, temperature, Lewis acid, and alkali base (Tables S1–S5), different (PNNP)Ir complexes as precatalysts were screened for CO 2 hydrogenation (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We kicked off the project by investigating the possibility of CO 2 hydrogenation in alcoholic solvents, as similarly reported by Klankermayer and Beller, where acidic conditions were used by adding Al­(OTf) 3 or bistriflyl imide derivatives. In contrast, to be emphasized is that our system for CO 2 hydrogenation shows high reactivity under basic conditions (utilizing catalytic alkali base, vide infra and Table S5), capitalizing on our previous methods for the activation of (PNNP)­Ir precatalysts to initiate the catalyst vitalized by the positive effects of alkali bases in alcohols. , After an initial optimization of solvent, pressure, temperature, Lewis acid, and alkali base (Tables S1–S5), different (PNNP)Ir complexes as precatalysts were screened for CO 2 hydrogenation (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…With these points in mind, we set out to investigate the hydrogenation of CO 2 to MeOH using highly sterically encumbered (PNNP)­M complexes (M = Ir, Ru, Fe), which we have developed for the hydrogenation of mono- and polycarboxylic acids through ester/lactone intermediates , and for photoreduction of CO 2 to formate (HCO 2 – )/formic acid (HCO 2 H) . Among them, due to the inherent robustness of tetradentate PNNP-coordinated iridium (Ir) catalysts (Figure b) toward both heat and light energies, we assumed that (PNNP)Ir complexes would be promising candidates to achieve hydrogenation of CO 2 in the presence of alcohol at elevated temperatures through a cascade of orthogonal reduction–esterification–reduction processes: CO 2 hydrogenation to HCO 2 H followed by esterification of HCO 2 H and subsequent hydrogenation of the resulting alkyl formate to MeOH.…”
Section: Introductionmentioning
confidence: 99%
“…4,25–28 Mechanochromophores are molecules wherein chemoselective rearrangements proceed accompanied by optical changes in response to mechanical stress. 29–33 As such, they are ideal tools to obtain crucial information on sacrificial bonds by virtue of their self-reporting capability. 34–37 However, introducing mechanophores into elastomers alters the properties of the original materials, as the activation energy of mechanophores is typically lower than those for the cleavage of representative C–C bonds, which means that the results may not accurately reflect the intrinsic properties of the DN elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…Masaoka investigated photocatalytic activity of a series of (tpy)­Ru­(L)­(CH 3 CN) complexes by varying bidentate ligands L, realizing selective CO production with the TON of up to 353 (Figure a, (ii)). , (CNC)­Ru­(bpy)­(L) complexes (bpy = 2,2′-bipyridine) were also developed by Papish and co-workers (Figure a, (iii)) . Saito reported that an Ir complex having a PNNP-tetradentate ligand works as a robust photocatalyst, achieving the TON of 2550 after 150 h for preferential production of HCOOH over CO (HCOOH/CO = 4.4/1) (Figure a, (iv)) . Han recently reported an iron–purpurin photocatalyst, which possesses an organic dye as a light-absorbing ligand on iron and exhibits high catalytic activity for selective formation of CO with a TON of over 2000 in 120 h (Figure a, (v)) .…”
mentioning
confidence: 99%